Predicting Financial Distress in Bangladesh’s Private Commercial Banks: An Altman Z-Score Approach - Supty, Jannatul Ferdousy; Milon, Md. Aminul Islam; Rahman, Md. Mostafijur; Jalal, Md. Shah (Asian Business Review, 2025)
The research study focuses on evaluating the financial distress of the private commercial banking industry in Bangladesh. This research focuses on 11 crisis-hit private commercial banks in Bangladesh, spanning the period from 2018 to 2023, and employs the Altman Z-score approach. The study applies key financial ratios, including working capital to total assets, retained earnings to total assets, operating earnings to total assets, and book value of equity to total liabilities, to examine financial soundness. The research has revealed that 10 out of 11 selected banks fall within the distress zone, with Bangladesh Commerce Bank Limited and National Bank Limited being the most distressed. Only one bank, under the Grey Zone, indicating financial instability but not immediate trouble, is Union Bank PLC. The primary reasons for financial instability are liquidity shortages and declining profitability, indicating a pressing need for improved risk management and regulatory guidelines. The researchers aim to provide policymakers, investors, and banking professionals with enhanced policy considerations and critical insights to mitigate risks and promote financial stability in Bangladesh's private commercial banking sector. Future researchers should focus on all banks operating in Bangladesh and cover a broader range of data.